Observations for Assertion-based Scenarios in the context of Model Validation - Aydal, Emine; Paige, Richard; Woodstock, Jim (Electronic Communications of the EASST, 2008)
Certain approaches to Model-Based Testing focus on test case generation from assertions and invariants, e.g., written in the Object Constraint Language. In such a setting, assertions and invariants must be validated. Validation can be carried out via executing scenarios wherein system operations are applied to detect unsatisfied invariants or failed assertions. This paper aims to improve our understanding of how to write useful validation scenarios for assertions in OCL. To do so, we report on our experiences during the creation and execution of 237 scenarios for validating assertions for the Mondex Smart Card application. We also describe key factors that must be considered in transforming scenarios into test cases.